AN ANALYSIS ON CODE-SWITCHING AND MIXING AMONG ENGLISH LEARNERS OF GAYONESE-SPEAKING STUDENTS - Imam Munandar; Ramadhani Sukria (Jurnal As-Salam, 2021)
This research tries to find out types and their dominance of code-switching and code-mixing among EFL students with Gayonese backgrounds. This research also looks at whether a certain type of ethnic group is affluent to a specific type of code-switching and mixing. The employed method is a qualitative study, in which this study manages to identify a social phenomenon in a certain community. The data is obtained from the 13 participants in their conversations. Instruments used are observation, recording, transcribing to identify code-switching, and mixing. The result of this study shows that the participants, who are all entitled to Gayonese identity, employed all kinds of code-switching and mixing, which were extra-sentential, inter-sentential, and intra-sentential. All types of code-switching and mixing are apparent in all sets of conversations. Along with some previous research, this study affirms that there is little evidence that a certain type of ethnicity employs a certain dominant form of code-switching and mixing. There appear all types of code-switching and mixing, without one dominant type, is found in all sets of conversations. Thus, code-switching and mixing were believed to assist the learners to deliver them through to be completely understood and meaningful in the communication.